Research dissertation - Wagogo Edwin Samuel (Uganda Christian University, 2024)
This study examines the economic factors affecting the growth of Small and medium Enterprises ( SMES) in Mukono municipality. SMES play a crucial role in driving economic development , job creation, and poverty reduction in the country. To gain a comprehensive understanding of the factors influencing SME growth this research examines the impact of financial practices on the growth and development of SMEs in Mukono. The research involved data collection from a diverse sample of SMES in Mukono in various sectors like retail, services, manufacturing and agriculture and the financial practices used by the SMEs owners. The analysis of this data provides valuable insights into the financial practices used by the smes owner and how the affect the growth and development of the businesses. From a sample size of 100 respondents 50 responded and about 56% of smes owner in Mukono are male and 44% are females showin a fairly balanced gender representation among SME owners in Mukono. An overwhelming 98% of respondents reported that they maintain regular financial records for their business mostly using cash books, sales ledgers , purchase ledgers payroll records and financial statements. This study examines the relation between the financial practices used in SMEs and how they influence the growth and development of SMes in Mukono municipality. The Drivers of the growth and developed of the Smes identified by the respondents show 72% of the respondents identified the financial management practices as a major factor that strongly affects the business growth and 64% also identified market expansion as another key driver followed by 34% employee skills development and 32% with product innovation. The evaluation of the fiancial management practices shows that 60% majority of the respondents agreed that financial management practices were well organized and effective in the growth and development of their businesses. Therefore the findings indicate that financial management practices , particularly record keeping and cash flow management are critical to the growth and development of SMES in Mukono municipality. The lack of access of external financing remains a major obstacle for many SMEs largely due to high interest rates and collateral requirements. Therefore SMEs that regularly monitor their financial and implement effective financial management practices tend to experience better growth.
Under graduate dissertation